Role of Death in “The Small Town Sea” by Anees Salim - Parbhakar, Neha; Kumar, Sandeep; Krishan, Ram (International Journal of Psychosocial Rehabilitation, 2020)
Death is the crucial part of life. Death brings out the emotional feelings of humanity. Anees Salim reflects the human’s emotional response to death through the character of thirteen years old child narrator, who recounts his experience after his father’s death. Death is associated with aloneness, love, fear and decay. In this paper, we shall study what is the effect of death on life and it will also highlight the human experience of death and decay. It represents a dominant theme of death in Anees Salim’s novel The Small Town Sea, and express the sensitive correlation between the dead person and his close relatives. Anees Salim’s style of writing in this novel reveals his viewpoints regarding life and death. This novel shows that in spite of the inevitability of death, people struggle to live. As in this novel, the protagonist’s dying father moves to his hometown to spend his last days, closing to death.